If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -25 = 11x + 17 Reorder the terms: -25 + 8x = 11x + 17 Reorder the terms: -25 + 8x = 17 + 11x Solving -25 + 8x = 17 + 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. -25 + 8x + -11x = 17 + 11x + -11x Combine like terms: 8x + -11x = -3x -25 + -3x = 17 + 11x + -11x Combine like terms: 11x + -11x = 0 -25 + -3x = 17 + 0 -25 + -3x = 17 Add '25' to each side of the equation. -25 + 25 + -3x = 17 + 25 Combine like terms: -25 + 25 = 0 0 + -3x = 17 + 25 -3x = 17 + 25 Combine like terms: 17 + 25 = 42 -3x = 42 Divide each side by '-3'. x = -14 Simplifying x = -14
| 12x=20x-14 | | 15x-10=6x+20 | | 24-5x=5x+24 | | -1+11a=-b-18 | | 69+2(-8+2g)=1-g | | -x-24=0 | | 6m+4m=180 | | 3(12f-10)=4f-1 | | 1.06w-3=0.71 | | 104+10x-4+76+104=360 | | 100-50=X | | 2x-67=90 | | 4n=4n+12 | | 65+53+97+x=360 | | (6x^2)-13x=8 | | 100+50=180 | | 60=4X+8Y | | 45+82+x=180 | | 2x+5y=1440 | | y+y+5w=2(y+3w) | | V=h(18-2h)(12-2h) | | 9x+11+x=91 | | 6x+9=3x+27 | | 6(7-2*1.44)=5*1.44+1 | | 11x-64=13 | | 100+50=X | | 3n^4*6n^6= | | 8-8(m+6)=-96 | | t-13=18 | | 7x+34=55 | | 8(1+7x)=344 | | 3(x-5)=5x-11 |